Do Urban Design qualities add to property values? An empirical analysis of the relationship between Urban Design qualities and property values. (March 2020) - Hamidi, Shima; Bonakdar, Ahmad; Keshavarzi, Golnaz; Ewing, Reid
Abstract: Urban design qualities have the potential to contribute to the sense of safety, comfort, engagement, and overall neighborhood satisfaction perceived by residents, thus can be related to higher property values. Yet, many of these urban design qualities are highly conceptual, require extensive data collection and are subject to various interpretations. As a result, there is little empirical evidence on how street-level urban design qualities are related to property values. Drawing on Multi-level Modeling, this article employs a highly cited dataset on urban design qualities in New York City to provide a statistical analysis of the direct relationship between these qualities and property values. Controlling for confounding factors, this article identifies "imageability" in the street-level environment as a featured urban design quality with the most statistically significant association with property values. In addition, research findings suggest that "transparency" of building facades are positive predictors of property values, whereas the complexity of the built environment exhibits a negative correlation with property values. Policy implications for planners, urban designers, and developers include designing guidelines and street layouts that encourage memorable civic image and identity. While investing in building facades with greater transparency would yield higher property values, complexity in the urban environment, particularly in neighborhoods seeking investment and attracting capital should be treated with care by all parties involved. Highlights: Imageability and transparency are significant predictors of property values. Excessive complexity in streets could adversely impact property values. Human scale and enclosure are not significantly associated with property values. Developers may benefit from investing in iconic and imageable buildings as well as constructing transparent facades.